1997
DOI: 10.1103/physrevlett.79.1447
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Excited State in11LiatEx=<

Abstract: Inelastic scattering data of 11 Li from hydrogen at 68A MeV have been interpreted as the excitation of a state in 11 Li at E x 1.3 MeV, with an assignment of J p 3 2 1 . Analysis of those data in a distorted wave approximation assuming transitions to three candidates obtained in a ͑0 1 2͒hv shell model suggests an alternative nuclear shakeoff mechanism.[S0031-9007(97)03915-X]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 18 publications
7
64
0
Order By: Relevance
“…Further, in the calculations we use the LSSM density for the 9 Li cluster with rms radius R c =2.31 fm [43] and for the h-halo we probe two densities: the one being described by the Gaussian function (G density) (e.g., [61])…”
Section: Results Of Calculations For Breakup Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, in the calculations we use the LSSM density for the 9 Li cluster with rms radius R c =2.31 fm [43] and for the h-halo we probe two densities: the one being described by the Gaussian function (G density) (e.g., [61])…”
Section: Results Of Calculations For Breakup Processesmentioning
confidence: 99%
“…This difference can affect the results for the cross sections in the region of relatively large angles of scattering. This point was one of the reasons the LSSM densities [43] for 9,11 Li to be used in our work.…”
Section: A Microscopic Reopmentioning
confidence: 96%
“…There are only two or three fitting parameters in the hybrid model that are related to the depths of the ReOP, ImOP and the spin-orbit part of the OP. Along with some phenomenological density distributions for He and Li isotopes we have used in our works realistic microscopic density obtained within the large-scale shell model (LSSM) [48,49]. In the present work devoted to processes with 10,11 Be nuclei we use the density distribution for 10 Be obtained within the QMC model [50,51] and also the densities of 10 Be and 11 Be obtained within the GCM [52].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, for scattering from light nuclei, they used a Helm model to obtain longitudinal form factors. Therein densities obtained from no-core shell model calculations [5,6] also were used. With the He isotopes, they found that the charge density of 6 He differed from that of 4 He but that of 8 He was not significantly different to that of 6 He.…”
mentioning
confidence: 99%